PEMBUBARAN PERKAHWINAN KERANA MENGAHWINI WANITA DALAM IDDAH OLEH MAHKAMAH TINGGI SYARIAH KUALA TERENGGANU - Ibrahim, Basri; Syed Abd Rahman, Syed Mohd Azmi (Jurnal Syariah, 2009)
Islam promotes marriage and it is one of Prophet Muhammad’s sunnah. Unless allowed according to syarak, not all Muslim woman can be married. Among of them are those whom still bound to talaq raj'i iddah waiting period. A marriage that overrule this term is fasid marriage and is not legal. This article is to focus debates among Moslem scholars related to dissolution of marriage of a couple in Syariah High Court, Kuala Terengganu. Reason being is that to marry Muslim woman that is still bound to talaq raj‘i iddah waiting period is not allowed. Special focus on judgement done by Chief Judge, State Syariah Court of Terengganu, in regard to Nor Radhiah Bin Ramli vs Aziz Bin Osman case. The dissolution of marriage by Syariah Hight Court is base on existing enactment which follows al-Shafi‘i path.